Nutritional aspects in the management of gestational Diabetes mellitus (Research, Society and Development, 2023)
Diabetes mellitus is characterized as a pathology that can be found mainly in three different types, and among these is gestational diabetes mellitus (GDM). GDM develops during pregnancy from insulin resistance and presents some risk factors for its development, such as obesity and overweight, family history and advanced maternal age. Thus, the objective is to understand its pathology and the role of nutrition in treatment and prevention, based on reading articles and carrying out an integrative literature review. The risks that this type of diabetes can generate to the health of the mother and the fetus are presented, such as pre-eclampsia, predisposition to the development of type 2 diabetes mellitus, macrosomia and greater risks of obesity. From the understanding of these points, nutritional monitoring is understood as effective in the prevention and treatment of gestational diabetes. The low glycemic index diet, DASH and the Mediterranean diet are efficient in glycemic control during gestational diabetes and also occur in the prevention of this pathology, in order to promote pregnancies without major intercurrences and healthier eating habits.